Wilms tumor in a left pelvic kidney: A case report. (2020) - Oyinloye, Adewale Olaotan; Wabada, Samuel; Abubakar, Auwal Mohammed; Oyebanji, Lateef O.; Rikin, C.U.
Highlights: Nephroblastoma is the most common pediatric renal tumor. Genitourinary anomalies and syndromes frequently co-exist. The existence of Wilms tumor in association with unilateral pelvic renal ectopia is very rare. Nephroblastoma in a left pelvic kidney presenting as lower abdominal mass in a 10 year old is presented. Abstract: Introduction: Wilms tumor(nephroblastoma) is the most common renal tumor in childhood.The most frequent anomalies and syndromes associated with this tumor involve the genitourinary tract. The occurrence of Wilms tumor with renal ectopia is rare.When present, Wilms tumor is usually found in association with other forms of renal ectopia like horseshoe kidneys or crossed fused renal ectopia. However, reports of the occurrence of Wilms tumor in unilateral pelvic renal ectopia is uncommon. We report a case of Wilms tumor in a pelvic left kidney. Presentation of case: A 10 year old girl presented to the out-patient department with a one year history of lower abdominal mass, pain and hematuria. Examination revealed a mass in the suprapubic region. Radiological investigations showed a tumor in a left pelvic kidney. She was managed with preoperative chemotherapy, surgery and adjuvant chemotherapy. Histopathologic examination of the nephrectomy specimen confirmed the diagnosis of nephroblastoma. Discussion: The occurrence of Wilms tumor in association with renal ectopia is rare. There are few reports of tumors arising in unilateral pelvic ectopic kidneys. A multi-modal treatment approach involving the use of chemotherapy, surgery and radiotherapy (for high-risk tumors) in the management of Wilms tumor gives good outcome. Conclusion: Tumors arising from a pelvic kidney should be considered as part of the differential diagnosis of lower abdominal masses in children.